2010
DOI: 10.1175/2009jcli3200.1
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization and Trend Analysis of Canadian Near-Surface Wind Speeds

Abstract: Near-surface wind speeds recorded at 117 stations in Canada for the period from 1953 to 2006 were analyzed in this study. First, metadata and a logarithmic wind profile were used to adjust hourly wind speeds measured at nonstandard anemometer heights to the standard 10-m level. Monthly mean near-surface wind speed series were then derived and subjected to a statistical homogeneity test, with homogeneous monthly mean geostrophic wind (geowind) speed series being used as reference series. Homogenized monthly mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
3
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(212 citation statements)
references
References 37 publications
4
197
3
8
Order By: Relevance
“…, and the declines in annual mean SWS were matched by increases in the percentage of calm conditions and by decreases in high wind speeds (Tuller 2004). Based on the credibility of the raw wind dataset from Canada, Wan et al (2010) homogenized monthly mean SWS series by adjusting all significant mean shifts and identified significant reductions in SWS throughout western Canada and most parts of southern Canada from 1953 to 2006 (Fig. 3b).…”
Section: North Americamentioning
confidence: 98%
See 2 more Smart Citations
“…, and the declines in annual mean SWS were matched by increases in the percentage of calm conditions and by decreases in high wind speeds (Tuller 2004). Based on the credibility of the raw wind dataset from Canada, Wan et al (2010) homogenized monthly mean SWS series by adjusting all significant mean shifts and identified significant reductions in SWS throughout western Canada and most parts of southern Canada from 1953 to 2006 (Fig. 3b).…”
Section: North Americamentioning
confidence: 98%
“…A significant decrease in SWS has been observed in the Western Plains region, where the SWS during the spring has decreased by 20% over the past 30 years (Green et al 2012). Furthermore, the most significant decrease in SWS from 1989 to 1998 occurred in Wisconsin Wan et al (2010)) and reached − 0.51 m s −1 decade −1 , whereas weak declines (smaller than − 0.09 m s −1 decade −1 ) occurred in the southwestern region of Idaho (Reba et al 2011), the American Midwest (Abhishek et al 2010), the southern region of California (Rasmussen et al 2011). Malloy et al (2015) reported a clear slowdown in SWS in the southeastern United States, whereas Mahowald et al (2007) reported an SWS reduction of only − 0.08 m s −1 decade −1 in the southern United States.…”
Section: North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of correspondence between observational and reanalysis data sets and between observational data sets may derive from differences in time-series duration (and the short time-series of wind speed that are available for analysis), changes in station location, measurement height, data recording procedures and instrumentation deployed, in addition to difficulties in developing homogeneous observed records of near-surface wind speed (Pryor et al, 2009;Fu et al, 2011;Wan et al, 2010). Further, mid-latitude wind speeds exhibited high variability at interannual to interdecadal time scales linked to seasonal variation of the atmospheric circulation and internal modes of climate variability (Enloe et al, 2004;Pryor et al, 2005, Park et al, 2010Pryor and Ledolter, 2010) which further confounds identification of robust trends and attribution thereof.…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
“…with wind velocity v, anemometer height h, and an exponent λ = 1/7 as discussed in Wan et al (2010). Inhomogeneities in meteorological times-series can be identified by finding an optimal solution to the multiple breakpoint problem.…”
Section: Wind Gust Datamentioning
confidence: 99%